Investigation of autistic traits through strategic decision-making in games with adaptive agents - Alexis B. Craig (Nature Portfolio, 2017)
Abstract Autism Spectrum Disorders are characterized by difficulties in communicating and cooperating with other people. Impairment in Theory of Mind (ToM), the ability to infer what another person is thinking, may contribute to these social deficits. The present study assesses the relationship between autistic traits and decision-making in a socioeconomic game environment that measures ToM and cooperation. We quantified participant strategy during game play with computer agents that simulated aspects of ToM or fixed strategy agents with static behaviors or heuristics. Individuals with higher Autism Quotient (AQ) scores cooperated less than subjects with low AQ scores with the ToM agents. In contrast, subjects with higher AQ scores cooperated more with fixed strategy agents. Additionally, subjects with higher AQ scores spent more time than low AQ subjects signaling cooperative intent in games with fixed strategy agents while spending less time signaling cooperation with adaptive agents, indicating a preference toward systemizing behaviors in the face of uncertainty. We conclude that individuals with high levels of autistic traits are less likely to utilize ToM as a cognitive strategy, even when it is beneficial, to achieve a desired outcome.